PERBANDINGAN PENGELOLAAN RUANG TERBUKA HIJAU KOTA SEMARANG DAN KOTA SURABAYA TAHUN 2010-2015 - Herati Puri; Turtiantoro . (Journal of Politic and Government Studies, 2017)
Abstract. Green Open Space is an importat element in creating qualified city in realizing ecological city in order of ecological city realization. The government policy related to the 30% proportion provision constitute the minimum size in an effort to ensure an urban development balance. Management of green open space is one of general policy and regional development programs in environment space sector by the municipality to fulfill extents of green open space. Manajement of green open space in the city of Semarang and Surabaya is done through of planning, organizing, directing, and monitoring. Research method uses descriptively qualitative approach with observation, interview, and literary review as the data collecting technique. The interviewees are Sub Field Head of Spatial Planning and Environment of Bappeda Semarang, Landscape Gardening Division Head of Hygiene and Landscaping Gardening Department of Semarang, Sub Section Head of Spatial Planning, Housing and Environment of Bappeko Surabaya, Staff of Green open Space Planning of Hygiene and Green Open Space of Surabaya In the manajement comparative of green open space in the city of semarang and Surabaya in 2010-2015, the are similarities and differences. Differences in management of Green Open Space in Semarang and Surabaya there is in quality of human resources, leadership style, budget and the involvement of private sector. The presence of this research can be used as an input in the management of Green Open Space in the city of Semarang and Surabaya Recommendation could be done to Semarang city is to improve the quality of human resources of relevan agencies and conducting CSR with private sector. Whereas the recommendation could be done to Surabaya city is to give strict punishment for the people who founded illegal building on land designated as Green Open Space. Keywords : Green Open Space, manajement, comparative